2016
DOI: 10.1088/1741-2560/13/5/056005
|View full text |Cite
|
Sign up to set email alerts
|

Decoding intravesical pressure from local field potentials in rat lumbosacral spinal cord

Abstract: Chronic monitoring of intravesical pressure is required to detect the onset of intravesical hypertension and the progression of a more severe condition. Recent reports demonstrate the bladder state can be monitored from the spiking activity of the dorsal root ganglia or lumbosacral spinal cord. However, one of the most serious challenges for these methods is the difficulty of sustained spike signal acquisition due to the high-electrode-location-sensitivity of spikes or neuro-degeneration. Alternatively, it has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 36 publications
0
16
1
Order By: Relevance
“…The average correlation coefficients for saline trials and acetic acid trials for real-time estimation (Table II) are higher than two previous offline studies where correlation coefficients were reported (0.81 in Ross et al and ~0.82 in Im et al) [9], [10]. The higher bladder decoding correlations in our study suggest that our Kalman model provides an improved approach over prior studies, particularly in tracking relative changes in bladder pressure.…”
Section: Discussioncontrasting
confidence: 64%
“…The average correlation coefficients for saline trials and acetic acid trials for real-time estimation (Table II) are higher than two previous offline studies where correlation coefficients were reported (0.81 in Ross et al and ~0.82 in Im et al) [9], [10]. The higher bladder decoding correlations in our study suggest that our Kalman model provides an improved approach over prior studies, particularly in tracking relative changes in bladder pressure.…”
Section: Discussioncontrasting
confidence: 64%
“…One concern about dorsal horn recording is the risk of tissue reaction or spinal compression due to the invasive technique applied in this experiment 19 . However, using just one single electrode minimizes this risk.…”
Section: Discussionmentioning
confidence: 99%
“…This is the principle issue to be investigated in this paper. The sensory signals recorded from dorsal horn of spinal cord have been used previously for detecting the sensory events generated by electrical stimulation 18 and decoding intravesical pressure in rat 19 .…”
Section: Introductionmentioning
confidence: 99%
“…While on-demand pelvic nerve stimulation at prestipulated timepoints can help to empty the bladder, available on-line information about the fullness of the bladder could enable more flexible on-demand scheduling, and more effective delivery of stimulation under a closed-loop neuromodulation scheme 21 . Other than implanting devices that detect bladder size or pressure changes directly 32 , previous studies have shown that it was possible to correlate intravesical pressures with in vivo neural recordings obtained from the pelvic nerve [33][34][35] , pudendal nerve 36 , dorsal root ganglion 37 , and lumbar/sacral roots [38][39][40][41] in various species (e.g. mice, rats, cats, and pigs).…”
Section: Discussionmentioning
confidence: 99%